2020
DOI: 10.1088/1755-1315/593/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Coral Cover and The Associated Reef Fishes Abundance in Enggano Island Bengkulu

Abstract: The coral reef is the habitat for more than a million marine species. The damage of the coral reef could decrease associated marine biodiversity, and the coral reef fishes are one of the groups impacted by the coral reef destruction. This study aimed to measure the coral coverage, to estimate the abundance of coral fishes, and to determine the correlation between coral coverage and abundance of coral reef fishes in Enggano Island, Bengkulu. The line intercept transect method was used by applying 25 m length tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…(63.1%). The effect of a percentage value of more than 60% on coral reef health is in line with the study by Kusuma et al (2020) that the effect of reef health on the abundance of coral fish on Enggano Island Bengkulu 0.615 (61.5%) was coral fish, affected by the health of corals. Similar results Rondonuwu et al (2019) reports high fish stock found in a high coral cover in western Halmahera, west Maluku province, Indonesia, in contrast to a low fish stock found in a low coral cover.…”
Section: Discussionsupporting
confidence: 89%
“…(63.1%). The effect of a percentage value of more than 60% on coral reef health is in line with the study by Kusuma et al (2020) that the effect of reef health on the abundance of coral fish on Enggano Island Bengkulu 0.615 (61.5%) was coral fish, affected by the health of corals. Similar results Rondonuwu et al (2019) reports high fish stock found in a high coral cover in western Halmahera, west Maluku province, Indonesia, in contrast to a low fish stock found in a low coral cover.…”
Section: Discussionsupporting
confidence: 89%
“…The abundance of carnivorous fish will balance the abundance of herbivorous fish and directly affect the abundance and species richness of reef fish (Figure . 3). Kusuma et al (2020), in their research on Enggano Island, stated that low coral cover causes a low abundance of fish. Coral reef fish are one of the fish that live permanently in coral reefs (Hoeksema, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Coral reef fish are one of the fish that live permanently in coral reefs (Hoeksema, 2017). Damaged coral reefs will cause a decrease in the abundance of reef fish (Kusuma et al, 2020). Nudibranchs are vulnerable to a large number of marine animals (Adiwijaya et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The range of Pomacentrus alexanderae spans Australia to Japan. Type Cirrhilabrus solorensis is endogenous, even Kusuma et al (2020) stated this is an endemic fish to Indonesia. According to (Allen and Adrim 2003), these species' distribution is only limited from Papua to Bali.…”
Section: Composition Of Reef Fishmentioning
confidence: 99%